Improving T-Shirt Folding Skills in Students with Intellectual Disabilities using Explicit Instruction - Tambunan, Florida Deswita; Budi, Setia (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study aims to evaluate the effectiveness of the Explicit Instruction method in improving the ability to fold clothes in students with disabilities in class V of SLB Negeri Pematang Siantar. This study uses the Classroom Action Research approach which is carried out in two cycles. Each cycle consists of four meetings that include the planning, action, observation, and reflection stages. The research subjects consisted of four students with mild disabilities who had difficulty folding clothes independently. Data were collected through initial capability tests, post-cycle tests I and II, as well as observation and documentation. The results showed that the use of the Explicit Instruction method succeeded in improving students' ability to fold clothes, with the average score increasing from 50% in the initial test to 72.5% in the post-cycle II test, exceeding the Minimum Completeness Criterion of 65%. The implication of this study is that Explicit Instruction can be applied effectively to teach practical life skills to students with disabilities, increasing their independence in daily life.